Light-dependent pathways for dopaminergic amacrine cell development and function - Teona Munteanu; Katelyn J Noronha; Amanda C Leung; Simon Pan; Jasmine A Lucas; Tiffany M Schmidt (eLife, 2018)
Retinal dopamine is a critical modulator of high acuity, light-adapted vision and photoreceptor coupling in the retina. Dopaminergic amacrine cells (DACs) serve as the sole source of retinal dopamine, and dopamine release in the retina follows a circadian rhythm and is modulated by light exposure. However, the retinal circuits through which light influences the development and function of DACs are still unknown. Intrinsically photosensitive retinal ganglion cells (ipRGCs) have emerged as a prime target for influencing retinal dopamine levels because they costratify with DACs in the inner plexiform layer and signal to them in a retrograde manner. Surprisingly, using genetic mouse models lacking specific phototransduction pathways, we find that while light influences the total number of DACs and retinal dopamine levels, this effect does not require ipRGCs. Instead, we find that the rod pathway is a critical modulator of both DAC number and retinal dopamine levels.